Mitigation of Natural Disasters as Efforts to Minimize Unwanted Impacts in Baleendah Sub-District, Bandung Regency, Indonesia - Yuyun Hidayat; Sukono Sukono; Kalfin Kalfin (Research Collaboration Community (RCC), 2021)
The Flood disaster is a natural event, one of which is caused by overflowing rivers. This disaster often occurs in the Majalaya area, Bandung Regency. Geographical conditions close to the Citarum River flow and the plains lower than the surrounding area causes this area to be flooded especially during the rainy season. Through the Community Service Program with the topic